"Taking America's Story to the World": Touring Jerome Robbins's Ballets: U.S.A. During the Cold War. Issue 2 (August 2020) - Prickett, Stacey
Abstract : Between 1958 and 1961, Jerome Robbins's Ballets: U.S.A. company toured to European arts festivals with a repertory of new and existing works, most of which remain in performance more than six decades later. Cold War political and artistic imperatives intersected in choreography that circulated visions of "American" innovation and youthful vitality, danced to an eclectic range of scores by a mixed-race cast. Archival documentation of the funding process reveals discussions about aesthetic priorities and the choreographer's responsibility to the US government. Analysis of press coverage of the performances also considers the extent to which diplomatic objectives were achieved.